2018
DOI: 10.1155/2018/8956404
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides/Glucose and Triglyceride/High-Density Lipoprotein Cholesterol Indices in Normal and Preeclamptic Pregnancies: A Longitudinal Study

Abstract: Metabolic changes have been correlated with adverse pregnancy outcomes. The aim of the present study is to determine the TyG and TG/HDL-c indices in a cohort of healthy pregnant (n = 142), preeclamptic (n = 18), and healthy nonpregnant women (n = 56). Preeclamptic women were selected from the same cohort. Pregnant women were followed during three periods of pregnancy and postpartum. The results showed a significant increase in the values of TyG and TG/HDL-c (p < 0.01) as pregnancy progresses, without significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
(49 reference statements)
1
16
0
1
Order By: Relevance
“…The present study showed that women who developed GDM had significantly increased TG/HDL-c ratios and TyG values in early pregnancy compared with controls; women with TG/HDL-c ratios or TyG values in the top tertile had a significantly higher risk of developing GDM and delivering LGA infants than did those with TG/HDL-c ratios or TyG values in the lowest tertile, suggesting that both TG/HDL-c and TyG at the time of the first trimester of pregnancy are independently and significantly associated with the later development of GDM and LGA infant delivery, which strengthens previous findings. [28][29][30] There were no statistical differences between TG/HDL-c and TyG in the ability of predicting the risk of GDM or LGA. The overall incidence of GDM (18.8%) in this study was slightly higher than that reported in a recent metaanalysis where the average incidence of GDM was estimated to be 15%.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The present study showed that women who developed GDM had significantly increased TG/HDL-c ratios and TyG values in early pregnancy compared with controls; women with TG/HDL-c ratios or TyG values in the top tertile had a significantly higher risk of developing GDM and delivering LGA infants than did those with TG/HDL-c ratios or TyG values in the lowest tertile, suggesting that both TG/HDL-c and TyG at the time of the first trimester of pregnancy are independently and significantly associated with the later development of GDM and LGA infant delivery, which strengthens previous findings. [28][29][30] There were no statistical differences between TG/HDL-c and TyG in the ability of predicting the risk of GDM or LGA. The overall incidence of GDM (18.8%) in this study was slightly higher than that reported in a recent metaanalysis where the average incidence of GDM was estimated to be 15%.…”
Section: Discussionmentioning
confidence: 80%
“…45 In our study, we did analyse an index combined TG and FPG-the TyG index, which has been reported to be closely associated with insulin resistance in general population, [24][25][26] as well as in pregnancies. 28 Furthermore, a recent study has reported that the relative risk of GDM and LGA infants in women in the top levels (> 66.6th percentile) of TyG index among the study population was 4.9-folds and 5.3-folds of its risk in women in the bottom levels. 30 Likewise, we also found women in the highest tertile of TyG index had a significantly higher risk of developing GDM and delivering LGA infants than women in the lowest tertile in this study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Poveda et al 22 studied a group of women in early, middle, and late pregnancy to determine TyG values in healthy and pre‐eclamptic pregnancies. They reported a mean TyG index of 8.3 in early pregnancy, slightly lower than the value determined in our study.…”
Section: Discussionmentioning
confidence: 99%